2018
DOI: 10.1177/1352458518795416
|View full text |Cite
|
Sign up to set email alerts
|

Can we trust self-reported walking distance when determining EDSS scores in patients with multiple sclerosis? The Danish MS hospitals rehabilitation study

Abstract: In MS patients with EDSS 4.0-7.5, 53% misclassified their walking distance yielding incorrect EDSS scores in 24%. Therefore, correct EDSS determination must be based on measurement of actual walking distance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 19 publications
3
12
0
Order By: Relevance
“…Several factors, such as fatigability, depression, and impaired sensory feedback, can influence the perceived exertion in PwMS [3]. These results corroborate with previous studies that have demonstrated perceived exertion disorders in PwMS and the importance of exploring their walking disabilities by standardized and objective measures [6,12]. These aspects should be considered in futures studies.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Several factors, such as fatigability, depression, and impaired sensory feedback, can influence the perceived exertion in PwMS [3]. These results corroborate with previous studies that have demonstrated perceived exertion disorders in PwMS and the importance of exploring their walking disabilities by standardized and objective measures [6,12]. These aspects should be considered in futures studies.…”
Section: Discussionsupporting
confidence: 88%
“…Understanding the severity of walking disorders in PwMS is essential for providing optimal medical care [5]. Although the Expanded Disability Severity Scale (EDSS) has been considered the gold standard for diagnosing the clinical and functional severity of MS, recent studies have highlighted its limitations and suggested that the EDSS should be supplemented by other objective standardized measurements [6]. The main limitation of the EDSS is that the walking capacity is self-reported by PwMS [7]; this subjective assessment with a possible reporting bias delivers information that could be influenced by cognitive deficits and desire to impress the healthcare provider [8].…”
Section: Introductionmentioning
confidence: 99%
“…In these groups, pwMS with unchanged EDSS (pEDSS = gmEDSS) and those with discrepant EDSS (pEDSS < or > gmEDSS), we found that progressive phenotype and higher scores in FSS and PHQ-9 increased the probability of inaccurate estimates of MWD and therefore belonged to the discrepant group. These data are consistent with the findings of Skjearbak et al [ 30 ], showing that the extent of misclassification of MWD increases in pwMS with fatigability and progressive phenotype and that depressive symptoms are related to self-perception of MWD; these findings emphasize the need to improve disability assessment especially in pwMS with moderate disability. Furthermore, a subgroup analysis conducted on the 75 patients in whom the obAS was calculated showed that GM® seems to effectively improve the accuracy of the MWD.…”
Section: Discussionsupporting
confidence: 92%
“…The upper arm function and the subtle cognitive deficits are underrepresented in the EDSS (46). Furthermore, the EDSS scores were mostly based on the walking distance reported by the patients, which might lead to an incorrect evaluation of the EDSS score (47).…”
Section: Discussionmentioning
confidence: 99%